Development and assessment of a novel hydrogen storage unit combined with compressed air energy storage - Erdemir, Dogan; Dincer, Ibrahim (PERGAMON-ELSEVIER SCIENCE LTD, 2023)
The present study concerns the development and performance assessment of a novel hydrogen storage system which is operated at a constant pressure where it is also integrated with a compressed air storage system to supply the necessary pressure needs. The uniqueness of the system is that there is a two-chamber storage system where air is stored in one chamber while hydrogen is stored in the other one. These two chambers work in a synchronized manner where one is compressed while the other one is expanded. In this regard, air is compressed in the air chamber to expand hydrogen for releasing to the fuel cell and vice versa. Integration of the compressed air storage into the present system helps keep the hydrogen storage chamber at the desired storage pressure. For this purpose, air is compressed into the chamber during the hydrogen discharging period, while air is released from the chamber during the hydrogen charging period. In order to exploit the additional benefit of the com-pressed air, an ammonia-fueled Brayton cycle is incorporated into the current system. Furthermore, this newly developed system is first analyzed thermodynamically by employing both energy and exergy approaches to confirm its conceptually correct functionality and write the balance equations for system analysis and secondly assessed for its performance through energy and exergy efficiencies. Moreover, the present results indicate that the compressed air as a part of the Brayton cycle covers the total energy demands of hydrogen compression and cooling. In terms of storage efficiencies, the energy and exergy efficiencies for the charging period are found to be 72.65% and 71.52%, while they become 35.3% and 35.24% for discharging period, respectively. The overall system energy and exergy efficiencies are calculated to be 35.00% and 34.38% for a period of 12 h charging and a period of 6 h discharging.
Keywords: Hydrogen; Compressed hydrogen storage; Energy storage; Compressed air storage; Exergy; Energy; Efficiency; EMPTYING PROCESS; PERFORMANCE; ELECTRICITY; SIMULATION; BEHAVIOR; TANKS; Thermodynamics; Energy & Fuels; Engineering; Mechanics